2006
DOI: 10.2460/ajvr.67.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 activity in the cerebrospinal fluid and serum of dogs with acute spinal cord trauma from intervertebral disk disease

Abstract: Data were consistent with results of experimental rodent spinal cord injury studies that indicate that MMP-9 is expressed early during secondary injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 24 publications
5
62
1
1
Order By: Relevance
“…Both the MFS 23 and CSF MBP concentration 13 have been previously associated with functional recovery in dogs with thoracolumbar IVDH and were shown via the logistic regression analysis to be independently related to outcome within the dogs in the present study; details of the findings regarding MBP concentration have been communicated in another report 13 about the same group of dogs. The collective impact of CSF CK activity, CSF MBP concentration, and MFS depends on case characteristics.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Both the MFS 23 and CSF MBP concentration 13 have been previously associated with functional recovery in dogs with thoracolumbar IVDH and were shown via the logistic regression analysis to be independently related to outcome within the dogs in the present study; details of the findings regarding MBP concentration have been communicated in another report 13 about the same group of dogs. The collective impact of CSF CK activity, CSF MBP concentration, and MFS depends on case characteristics.…”
Section: Discussionmentioning
confidence: 49%
“…Neurologic dysfunction was classified according to the MFS as follows: paraspinal hyperesthesia only (grade 5), ambulatory paraparesis and ataxia (grade 4), nonambulatory paraparesis (grade 3), paraplegia with intact nociception (grade 2), paraplegia with no superficial nociception (grade 1), and paraplegia with no deep nociception (grade 0). 22,23 After premedication of each affected dog, anesthesia was induced via IV administration of propofol a and anesthesia was maintained by use of inhalation anesthetic agents (sevoflurane b or isoflurane c ) for diagnostic imaging and collection of a CSF sample from the cerebromedullary cistern. Advanced imaging comprised myelography, computed tomography, or MR imaging; the type of imaging performed depended on access to equipment and clinician preference.…”
Section: Dogs With Acute Thoracolumbar Ivdh-betweenmentioning
confidence: 99%
“…Reported cerebrospinal fluid biomarkers include aspartate aminotransferase, calcium, glucose, nucleated cell count, protein, creatine kinase, lactate, myelin basic protein, matrix metalloproteinase 9, and tau protein. 139,[142][143][144][145][146][147][148][149] Witsberger and colleagues 139 published a screening method for clinical cases of acute SCI. In this study, combined elevation of myelin basic protein and creatine kinase in dogs with no detectable pain sensation following IVDH led to the probability of a successful outcome of 10%.…”
Section: Biomarkersmentioning
confidence: 99%
“…7 A small group of studies has demonstrated that inflammatory mechanisms may play a critical role in canine IVDH-associated SCI. [8][9][10][11] In particular, in acute canine SCI, resident microglial activation is prominent as is upregulation of matrix metalloproteinase 9, release of myelin basic protein, and overproduction of interleukin (IL)-6 and IL-8 messenger RNA (mRNA). [9][10][11][12] In order to further develop this model system, a broader understanding of inflammatory mechanisms after SCI is needed, particularly if pathways are to be targeted in preclinical trials.…”
Section: Introductionmentioning
confidence: 99%